Fenologian vaikutus aposemaattisen täpläsiilikkään (Arctia plantaginis) värimuotojen saalistuspaineeseen - Siirilä, Tuisku (2023)
Predation is a significant selection pressure on populations of prey species and as a result many species have evolved different defense mechanisms against predators. Various toxic, foul-tasting or smelly substances, spike and shield structures, and warning and protective colours are typical examples of defense mechanisms. Aposematic species use their warning colour to signal to predators that they are poisonous or otherwise poor-quality prey and thus try to avoid being targeted by the predators. The purpose of this study was to find out how predation pressure on the aposematic wood tiger moth (Arctia plantaginis) varies as the summer progresses and how the observed predation pressure is distributed between different colour morphs of A. plantaginis males. The study was carried out as a field predation experiment, where artificial model moths were used as prey. The models were made to resemble the three different colour morphs of adult A. plantaginis males found in Finland: two white morphs and one yellow. The model moths were pinned on tree trunks along the test transects and left in the field for three days. After this, the moths were picked up from the transects and checked for possible signs of attack and marked as either attacked or not attacked. In total, the exam consisted of 16 different transects, which were divided over an eight-week period. A transect count of birds was carried out from each transect, so that the possible effect of the structure of the local predator community on the predation pressure could also be examined. In this experiment, the progression of the summer or the colour morph were not found to affect the predation pressure of the wood tiger moth. The presence of certain bird species was found to increase the predation pressure of the transects, but the effect was evenly distributed among all colour morphs. The location of the transect was also found to affect the predation pressure in a statistically significant way. The forests in which the transects were located had varying characteristics and thus, based on this, no single factor can be named that would have influenced the strength of the predation pressure. Predation pressure can be determined by the sum of many different factors, and environmental conditions should not be ignored as a possible factor that has an influence on predation risk.